(untitled) (Italian Journal of Public Health, 2005)
Background. Nosocomial infections contribute substantially to increased morbidity, mortality and resource expenditure in Intensive Care Units (ICUs). Methods. A one-year prospective surveillance study was performed using epidemiological and microbiological methods to quantify the frequency of infections and the antimicrobial usage, microbiological environmental sampling and molecular typing of clinical and environmental isolates. Results. The frequency of ICU-acquired infections was comparable to other Italian ICUs. Most of these infections were caused by few epidemic clones of Pseudomonas aeruginosa, methicillin-resistant Staphylococcus aureus and Acinetobacter baumannii. The survival advantage of these epidemic clones over the sporadic isolates may be related to the multi-resistant profile of the epidemic clones and to the high usage of some antibiotics in the ICU. Hand contamination of ICU personnel is a likely factor for dissemination of epidemic clones within the ICU. Conclusions. The integrated surveillance approach described in this study is able to clarify the complex epidemiology of ICU-acquired infections and can provide important cues for prevention and control activities.